2020
DOI: 10.1111/jcmm.15274
|View full text |Cite
|
Sign up to set email alerts
|

Lung CSC‐derived exosomal miR‐210‐3p contributes to a pro‐metastatic phenotype in lung cancer by targeting FGFRL1

Abstract: Lung cancer has the highest mortality rate among human cancers, and the majority of deaths can be attributed to metastatic spread. Lung cancer stem cells (CSCs) are a component of the tumour microenvironment that contributes to this process. Exosomes are small membrane vesicles secreted by all types of cells that mediate cell interactions, including cancer metastasis. Here, we show that lung CSC‐derived exosomes promote the migration and invasion of lung cancer cells, up‐regulate expression levels of N‐cadheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 38 publications
(70 reference statements)
0
43
0
Order By: Relevance
“… 164 In a study on lung cancer, the researchers showed that exosomes derived from lung CSCs transferred cargo miR-210-3p to non-lung CSCs, which significantly contributed to the pro-metastasis phenotype. 162 Exosomal miR-210-3p upregulated the expression levels of N-cadherin, vimentin, MMP-9, and MMP-1, and downregulated E-cadherin expression in non-lung CSCs. 162 Mechanically, exosomal miR-210-3p promoted cancer cell metastasis by targeting FGFRL1.…”
Section: The Biological Roles Of Cscs-derived Evsmentioning
confidence: 98%
See 1 more Smart Citation
“… 164 In a study on lung cancer, the researchers showed that exosomes derived from lung CSCs transferred cargo miR-210-3p to non-lung CSCs, which significantly contributed to the pro-metastasis phenotype. 162 Exosomal miR-210-3p upregulated the expression levels of N-cadherin, vimentin, MMP-9, and MMP-1, and downregulated E-cadherin expression in non-lung CSCs. 162 Mechanically, exosomal miR-210-3p promoted cancer cell metastasis by targeting FGFRL1.…”
Section: The Biological Roles Of Cscs-derived Evsmentioning
confidence: 98%
“… 162 Exosomal miR-210-3p upregulated the expression levels of N-cadherin, vimentin, MMP-9, and MMP-1, and downregulated E-cadherin expression in non-lung CSCs. 162 Mechanically, exosomal miR-210-3p promoted cancer cell metastasis by targeting FGFRL1. 162 Hardin et al 165 investigated the roles of thyroid cancer stem-like cell-derived exosomal lncRNA MALAT1 and linc-ROR in thyroid cancer metastasis.…”
Section: The Biological Roles Of Cscs-derived Evsmentioning
confidence: 98%
“…This process is sustained by EVs via delivery and release of their targets into a target cell(s). Alongside tumor progression, EVs have the capability of carrying out other critical processes, including cell proliferation, tumor growth [ 76 ], angiogenesis [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], matrix remodeling, metastasis [ 75 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ], immune escape [ 69 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ], resistance to apoptosis [ 110 , 111 , 112 , 113 ], deregulation of energetic metabolism [ 114 , 115 , 116 , 117 ], sustaining proliferative signaling [ 94 , 118 , 119 , 120 ], evading growth suppression [ 121 , 122 , 123 ], deregulating and tumor-promoting inflammation [ 100 , 124 , ...…”
Section: Pathological Roles Of Evsmentioning
confidence: 99%
“…In another study, EV miR-105 was reported to stimulate invasion in both the respiratory and central nervous systems by inhibiting ZO-1 in endothelial cells, leading to enhanced cell migration [ 143 ]. Furthermore, it has been observed that EV miR-21 stimulates invasion of esophageal tumor cells by activating the programmed cell death 4 (PDCD4)/ c-Jun NH 2 -terminal kinase (JNK) axis [ 90 ].…”
Section: Pathological Roles Of Evsmentioning
confidence: 99%
See 1 more Smart Citation